Keperluan Motivasi dalam Pengurusan Kerja Berkualiti dari Perspektif Pemikiran Islam - Tengku Kasim, Tengku Sarina Aini; Mansor, Fadillah (Jurnal Usuluddin, 2007)
Quality work management begins with the process of planning, organizing, leading, and monitoring the activities by members of an organization to achieve the established objectives. An organization would not be able to operate smoothly without quality work management. The work management quality in Islamic perspective emphasizes that an organization should operate on the right path by not only looking into wealth and profit but also permissible of Allah as the principal objective. Dedicated and hard working employee who strive for his or her and the organization success is the biggest asset for a quality work management. Highly motivated employee will always strive for the best in order to provide excellent contribution to the organization. The significance of having motivational employee in a quality work management could not be denied. So many benefits could be acquired from the contribution provided. In addition, labor issues such as workforce and time wastage, laziness, lack of integity and regressive behaviour could be edged off.